English as Lingua Franca; A Threat to Multilingualism - Yoga Prihatin (Universitas Pancasakti Tegal, 2014)
Linguistic imperialism is often seen in the context of cultural imperialism. This article is intended to describe some teories of English as a lingua franca that can be a threat to multilingualism to some extent. The endangerd language project predicts that half of the world 6,500 languages by the end of the century and that the major reason of people learning national language and lingua franca (Han Rausing 2008). The following three princliples would help retain local languages on the other hand validate and promote multilingualism on the other; First, wherever possible, the mother tounge should be used as the medium instruction; other wise a local language shoud be used. Second, English can be happily be delayed until the later years of primary school. Thridly, the goal of Learners of English in multilingual and lingua franca setting should be multilingual performance and profeciency, not an idealized native-like profeciency.